A manganese sand-based ceramic catalytic membrane for water treatment and a preparation method thereof

By using the preparation method of combining manganese sand with matrix material, the problems of insufficient catalytic capacity and high cost of inorganic ceramic catalytic film are solved, and a manganese sand-based ceramic catalytic film with high catalytic activity and structural strength are prepared.

CN119075704BActive Publication Date: 2025-03-21XI'AN POLYTECHNIC UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411571920.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-21
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The existing inorganic ceramic catalytic films have problems such as insufficient catalytic capacity, easy cracking and falling off of the catalyst, and high preparation costs.

Method used

Manganese sand is used as the effective component of the ceramic catalytic film, and a manganese sand-based ceramic catalytic film is prepared by grinding natural manganese ore, mixing with the matrix material, pressing and sintering through step temperature-raising procedures.

Benefits of technology

The catalytic capacity has been improved. The manganese sand-based ceramic catalytic film has good catalytic activity on ozone and persulfate, and can effectively oxidize organic pollutants in water. It has a high structural strength, no risk of cracking or shedding, and has low preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119075704B_ABST
    Figure CN119075704B_ABST
Patent Text Reader

Abstract

The present invention relates to a manganese sand-based ceramic catalytic membrane for water treatment and a preparation method thereof, the preparation method comprising the following steps: S1: grinding natural manganese ore to a preset particle size to obtain manganese sand; S2: mixing the manganese sand and a matrix material to obtain a mixed material; wherein the mass percentage of the manganese sand is 40% to 60%; S3: pressing the mixed material under a preset pressure to obtain a preform; S4: sintering the preform through a step heating program to obtain a manganese sand-based ceramic catalytic membrane. The catalytic ability of the manganese sand-based ceramic catalytic membrane prepared by the present invention comes from the Fe and Mn elements rich in manganese sand, has good catalytic activity for ozone and persulfate, can effectively oxidize organic pollutants in water, and the manganese sand and the matrix material are pressed and sintered into one, the structural strength is large, there is no risk of cracking or falling off, the preparation method is simple, the manganese sand material is easy to obtain, and the preparation cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and in particular relates to a manganese sand-based ceramic catalytic membrane for water treatment and a preparation method thereof. Background Art

[0002] Membrane separation is an effective method for removing organic matter from water. Traditional membrane separation methods remove organic matter from water through the adsorption and interception of organic matter by organic polymer membranes, but it is prone to membrane pollution problems, resulting in reduced membrane flux and removal efficiency of organic polymer membranes.

[0003] Inorganic ceramic catalytic membranes are formed by combining catalysts on the surface and pores of ceramic membrane supports through physical deposition, surface coating, impregnation, etc. Inorganic ceramic catalytic membranes have the characteristics of strong chemical stability, high mechanical strength, reusability, and long life, and have greater application value than organic polymer membranes.

[0004] However, the surface and pores of the ceramic membrane support can only load a limited amount of catalysts, and the inorganic ceramic catalytic membrane still has the problem of insufficient catalytic capacity. In addition, due to the limitations of existing preparation processes, the inorganic ceramic catalytic membrane also has the problem of catalysts being easy to crack and fall off and high preparation costs. Summary of the invention

[0005] In order to solve the above problems existing in the prior art, the present invention provides a manganese sand-based ceramic catalytic membrane for water treatment and a preparation method thereof. The technical problem to be solved by the present invention is achieved by the following technical solutions:

[0006] The first aspect of the present invention provides a method for preparing a manganese sand-based ceramic catalytic membrane for water treatment, comprising the following steps:

[0007] S1: grinding natural manganese ore to a preset particle size to obtain manganese sand;

[0008] S2: mixing the manganese sand and the matrix material to obtain a mixed material; wherein the mass percentage of the manganese sand is 40% to 60%;

[0009] S3: Pressing the mixed material under a preset pressure to obtain a preform;

[0010] S4: Sintering the preform through a step temperature increase program to obtain a manganese sand-based ceramic catalytic membrane.

[0011] In one achievable manner, the matrix material includes: Al2O3;

[0012] The particle size of the matrix material is 100nm~1000nm.

[0013] In one achievable manner, the following is further included between step S2 and step S3:

[0014] Adding an auxiliary agent to the mixed material; the mass percentage of the auxiliary agent is less than or equal to 10%; the auxiliary agent includes: one or more of an adhesive, a lubricant and a performance optimizer.

[0015] In one achievable manner, the adhesive comprises: sodium carboxymethyl cellulose;

[0016] The lubricant includes: glycerol;

[0017] The performance optimizer includes: CuO.

[0018] In one achievable manner, the preset pressure is 0.5 MPa to 150 MPa.

[0019] In one achievable manner, step S4 includes:

[0020] S401: calcining the preform at a temperature of 200° C. to 300° C. to obtain a calcined embryo body;

[0021] S402: raising the temperature to 500° C. to 700° C. to calcine the calcined embryo body to obtain a calcined embryo body;

[0022] S403: raising the temperature to 1000° C.-1200° C., sintering the calcined embryo body to obtain the manganese sand-based ceramic catalytic membrane.

[0023] In one achievable manner, the time for the roasting and the calcining is 0.5 h to 2 h;

[0024] The sintering time is 1h~4h.

[0025] In one achievable manner, the preset particle size is less than or equal to 15 μm.

[0026] The second aspect of the present invention provides a manganese sand-based ceramic catalytic membrane for water treatment, which is prepared by the preparation method provided by the first aspect of the present invention.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention uses manganese sand as an effective component of a ceramic catalyst membrane, and prepares a manganese sand-based ceramic catalyst membrane by mixing manganese sand and a matrix material, pressing the mixture, and sintering the mixture through a step temperature increase procedure. The catalytic ability of the manganese sand-based ceramic catalyst membrane prepared by the preparation method provided by the present invention comes from the Fe and Mn elements rich in the manganese sand, and the manganese sand has good catalytic activity against ozone and persulfate, and can effectively oxidize organic pollutants in water. In addition, the manganese sand and the matrix material are pressed and sintered into one, and the structural strength is large, and there is no risk of cracking or falling off. The preparation method is simple, the manganese sand material is easily available, and the preparation cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the steps of a method for preparing a manganese sand-based ceramic catalytic membrane for water treatment provided by an embodiment of the present invention;

[0030] Figure 2 This is a comparison diagram of pure water flux of the manganese sand-based ceramic catalytic membrane provided by an embodiment of the present invention;

[0031] Figure 3 is a comparison chart of the porosity of the manganese sand-based ceramic catalytic membrane provided by an embodiment of the present invention;

[0032] Figure 4 This is a comparison chart of the bending strength of the manganese sand-based ceramic catalytic membrane provided by the embodiment of the present invention;

[0033] Figure 5 This is a comparison chart of the removal effect of tetracycline by the manganese sand-based ceramic catalytic membrane provided in an embodiment of the present invention;

[0034] Figure 6 This is an optical picture of a manganese sand-based ceramic catalytic membrane for water treatment provided by an embodiment of the present invention;

[0035] Figure 7a~Figure 7f This is a SEM image of a manganese sand-based ceramic catalytic membrane for water treatment provided in an embodiment of the present invention;

[0036] Figure 8a~Figure 8b This is a particle size distribution diagram of manganese sand and Al2O3 in a manganese sand-based ceramic catalytic membrane for water treatment provided by an embodiment of the present invention;

[0037] Fig. 9 This is a diagram showing the removal effect of tetracycline at different concentrations by a manganese sand-based ceramic catalytic membrane for water treatment provided by an embodiment of the present invention;

[0038] Fig.10 This is a data graph of the anti-pollution performance of a manganese sand-based ceramic catalytic membrane for water treatment provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto.

[0040] Embodiment 1

[0041] The first aspect of this embodiment provides a method for preparing a manganese sand-based ceramic catalytic membrane for water treatment. Figure 1 , Figure 1 The present invention provides a method for preparing a manganese sand-based ceramic catalytic membrane for water treatment according to an embodiment of the present invention. The method for preparing a manganese sand-based ceramic catalytic membrane for water treatment provided in this embodiment comprises the following steps:

[0042] S1: Grinding natural manganese ore to a preset particle size to obtain manganese sand.

[0043] Specifically, natural manganese ore is a natural mineral containing iron and manganese oxides, has good catalytic ability, and can be obtained through commercially available manganese sand filter materials for water treatment or waste slag produced by the manganese mining industry. The pore characteristics of manganese sand-based ceramic catalytic membranes prepared from manganese sands of different particle sizes are different. The smaller the particle size of the manganese sand, the smaller the pores of the prepared manganese sand-based ceramic catalytic membrane. When the particle size of the manganese sand is too large, the manganese sand-based ceramic catalytic membrane is difficult to prepare successfully. Therefore, according to the use of the prepared manganese sand-based ceramic catalytic membrane, the natural manganese ore is ground to a preset particle size to meet different application requirements.

[0044] In one achievable manner, the preset particle size is less than or equal to 15 μm. In this case, the prepared manganese sand-based ceramic catalytic membrane is directly used as a symmetric membrane material.

[0045] Furthermore, the manganese sand is screened to remove particles whose particle size does not meet the requirements, so as to ensure the integrity and uniformity of the membrane structure and internal pores of the prepared manganese sand-based ceramic catalytic membrane. The structural characteristics and catalytic activity of natural manganese ore can be determined by detecting the content of minerals such as iron, manganese, aluminum, and silicon in manganese sand, as well as by catalytic ozone and persulfate PMS experiments, and natural manganese ore with stable structural characteristics and good catalytic activity can be selected based on the experimental results.

[0046] S2: Mixing manganese sand and base material to obtain a mixed material, wherein the mass percentage of manganese sand is 40% to 60%.

[0047] In this embodiment, the matrix material includes: Al2O3. The particle size of the matrix material is 100nm~1000nm.

[0048] In this embodiment, the following steps are included between step S2 and step S3:

[0049] Adding additives to the mixed material. The mass percentage of the additives is less than or equal to 10%. The additives include: one or more of an adhesive, a lubricant and a performance optimizer.

[0050] In this embodiment, the adhesive includes sodium carboxymethyl cellulose, the lubricant includes glycerol, and the performance optimizer includes CuO. The performance optimizer is used to enhance the catalytic performance of the manganese sand-based ceramic catalytic membrane.

[0051] In this embodiment, the mass percentage of the matrix material is 40% to 60%, and the content of the matrix material affects the membrane strength and catalytic performance of the prepared manganese sand-based ceramic catalytic membrane. Specifically, the higher the content of the matrix material, the greater the strength of the prepared membrane, but the catalytic performance will be affected. When the content of the matrix material is insufficient, the self-reaction of the manganese sand is too violent, and the surface of the prepared manganese sand-based ceramic catalytic membrane has obvious defects, such as peeling, bulging, cracks, etc., and the membrane strength is low.

[0052] S3: Press the mixed material under a preset pressure to obtain a preform.

[0053] In this embodiment, the mixed material is pressed by a static pressure, a uniaxial hydraulic pressure or other pressure equipment to obtain a preform. The preset pressure is 0.5 MPa to 150 MPa.

[0054] S4: Sintering the green sheet through a step temperature rising procedure to obtain a manganese sand-based ceramic catalytic membrane.

[0055] In this embodiment, step S4 includes:

[0056] S401: calcining the preform at a temperature of 200° C. to 300° C. to obtain a calcined embryo body. The calcination time is 0.5 h to 2 h.

[0057] S402: raising the temperature to 500°C to 700°C to calcine the calcined embryo to obtain a calcined embryo. The calcination time is 0.5h to 2h.

[0058] S403: raising the temperature to 1000°C to 1200°C, sintering the calcined body to obtain a manganese sand-based ceramic catalytic membrane. The sintering time is 1h to 4h.

[0059] Specifically, during roasting, the self-adsorbed water and structural water inside the manganese ore are removed, and during calcination, the crystal structure of the manganese ore is fully changed. After roasting and calcining, the unstable factors inside the manganese ore that affect the structure of the manganese sand-based ceramic catalytic membrane have been fully removed. Therefore, the structure of the manganese sand-based ceramic catalytic membrane obtained after sintering is stable and complete, and the components and pores are uniform. In this embodiment, two step temperatures are set, namely 200℃~300℃ and 500℃~700℃, and the temperature is finally raised to the sintering temperature, namely 1000℃~1200℃, so that the initial blank undergoes different structural changes at each temperature stage in the step heating program, ensuring that the prepared manganese sand-based ceramic catalytic membrane has good structural characteristics. In this embodiment, natural aging is also included before roasting, and the roasting, calcining and sintering atmospheres are all nitrogen or air.

[0060] Specifically, the determination of the step temperature and sintering time in the step heating program is related to the particle size of the raw material, the pore characteristics of the required membrane material, and the content of manganese sand. The smaller the particle size of the raw material, the higher the content of manganese sand, and the easier it is to sinter the manganese sand-based ceramic catalytic membrane. At this time, the sintering temperature and time should be reduced. On the contrary, the larger the particle size of the raw material, the lower the content of manganese sand, and the more difficult it is to sinter the manganese sand-based ceramic catalytic membrane, the temperature and duration should be increased. It should be noted that the sintering temperature of the Al2O3-based ceramic membrane in the prior art is above 1400°C, and even if an additive is added, the sintering temperature is above 1250°C. The final sintering temperature of the manganese sand-based ceramic catalytic membrane in this embodiment is 1000°C~1200°C, and the preparation method of this embodiment effectively reduces the sintering temperature. Furthermore, the time and temperature of roasting, calcining and sintering can be determined according to the phase change curve of manganese sand during roasting.

[0061] The second aspect of the present embodiment provides a manganese sand-based ceramic catalytic membrane for water treatment, which is prepared by the preparation method provided by the first aspect of the present embodiment, and includes: manganese sand and a matrix material, wherein the mass percentage of manganese sand is 40% to 60%. The manganese sand-based ceramic catalytic membrane for water treatment provided by the present embodiment uses manganese sand as an effective ingredient.

[0062] The present embodiment provides a method for preparing a manganese sand-based ceramic catalytic membrane for water treatment, using manganese sand as the effective component of the ceramic catalytic membrane, and preparing the manganese sand-based ceramic catalytic membrane by mixing manganese sand and a matrix material, pressing, and sintering through a step temperature increase program. The catalytic ability of the manganese sand-based ceramic catalytic membrane prepared by the preparation method provided in this embodiment comes from the Fe and Mn elements rich in manganese sand, and has good catalytic activity for ozone and persulfate, and can effectively oxidize organic pollutants in water. In addition, the manganese sand and the matrix material are pressed and sintered into one, and the structural strength is large, without the risk of cracking or falling off. The preparation method is simple, the manganese sand material is easy to obtain, and the preparation cost is low.

[0063] Embodiment 2

[0064] On the basis of Example 1, this example prepares manganese sand-based ceramic catalytic membranes under different conditions and characterizes them, so as to further illustrate the manganese sand-based ceramic catalytic membranes for water treatment provided in this example and the preparation method thereof.

[0065] In this embodiment, the preparation method of the manganese sand-based ceramic catalytic membrane for water treatment comprises the following steps:

[0066] Step 1: Crush and grind the natural manganese ore, and then sieve it after grinding to control the particle size of manganese sand to 5μm~10μm.

[0067] Step 2: Obtain Al2O3 with a particle size of 500nm, mix a certain mass percentage of manganese sand with Al2O3, and then add sodium carboxymethyl cellulose, glycerol and CuO to the mixture of manganese sand and Al2O3 according to the mass percentage of sodium carboxymethyl cellulose being 1%, the mass percentage of glycerol being 1%, and the mass percentage of CuO being 5%, and then completely mix them through a planetary ball mill to obtain a mixed material. In this embodiment, the mass percentages of manganese sand are 40%, 46%, 50%, and 60%, respectively.

[0068] Step 3: Transfer the mixed material to a disc mold and press it through a tablet press at a pressure of 150 MPa to obtain a round blank.

[0069] Step 4: Place the preform in a 60°C oven for 12 hours for natural aging. Transfer the preform after natural aging to a tubular furnace, heat it from room temperature to 250°C at a rate of 5°C / min, keep it warm for 1 hour, and roast it to obtain a roasted embryo. Then heat it to 650°C at a rate of 5°C / min, keep it warm for 1 hour, and calcine it to obtain a calcined embryo. Finally, heat it to the sintering temperature at a rate of 5°C / min for sintering, and cool it to room temperature after sintering to obtain a manganese sand-based ceramic catalytic membrane. The manganese sand-based ceramic catalytic membrane prepared in this embodiment has a diameter of 28mm and a thickness of 2mm. In this embodiment, the sintering temperatures are 1050°C, 1100°C, and 1150°C, respectively, and the sintering times are 1h, 2h, 3h, and 4h, respectively. In this embodiment, multiple manganese sand-based ceramic catalytic membranes were prepared by changing the mass percentage of manganese sand, sintering temperature and sintering time to illustrate the effects of the above three experimental parameters. In the experimental group with the mass percentage of manganese sand changed, the sintering temperature was controlled to be 1100°C and the sintering time was 4h. In the experimental group with the sintering temperature changed, the mass percentage of manganese sand was controlled to be 46% and the sintering time was 4h. In the experimental group with the sintering time changed, the mass percentage of manganese sand was controlled to be 46% and the sintering temperature was 1100°C.

[0070] The manganese sand-based ceramic catalytic membranes obtained from the above three experimental groups were characterized to compare the pure water flux, porosity, and flexural strength of the manganese sand-based ceramic catalytic membranes prepared under different parameters, and the catalytic effect of the manganese sand-based ceramic catalytic membranes was characterized by the tetracycline removal rate of the manganese sand-based ceramic catalytic membranes. The characterization results are shown in Figure 2~Figure 5 As shown in the figure, the mass percentage of manganese sand, sintering temperature and sintering time have an impact on the pure water flux, porosity, flexural strength and catalytic effect of manganese sand-based ceramic catalytic membrane. Figure 2~Figure 5 It can be seen that the greater the mass percentage of manganese sand, the higher the sintering temperature, and the longer the sintering time, the lower the pure water flux of the manganese sand-based ceramic catalytic membrane, the smaller the porosity, the greater the flexural strength, and the greater the tetracycline removal rate. When the sintering temperature in the experimental group that changed the sintering temperature was 1150°C, and when the mass percentage of manganese sand in the experimental group that changed the mass percentage of manganese sand was 50% and 60%, due to the high temperature and the high mass percentage of manganese sand, the pure water flux of the manganese sand-based ceramic catalytic membrane was too low, and the tetracycline removal rate was also affected by the pure water flux. When the mass percentage of manganese sand was 50% and 60%, compared with the mass percentage of manganese sand of 50%, the flexural strength decreased and the porosity increased slightly. The maximum pure water flux of the manganese sand-based ceramic catalytic membrane prepared in this embodiment is 726.59L / m 2 ·h·bar, the flexural strength is between 24.4Mpa and 42.35Mpa, and the tetracycline removal rate is between 60.7% and 84.3%.

[0071] Based on the characterization data of manganese sand-based ceramic catalytic membrane, the optimal parameters for preparing manganese sand-based ceramic catalytic membrane are 46% mass percentage of manganese sand, sintering temperature of 1100℃, and sintering time of 2h. The manganese sand-based ceramic catalytic membrane prepared under the optimal parameter conditions was characterized, and the characterization results are as follows Figure 6~Figure 10 As shown by Figure 6 It can be seen that the manganese sand-based ceramic catalytic membrane prepared under the optimal parameter conditions has a smooth appearance and no obvious defects. Figure 7a~Figure 7d The surface SEM images of manganese sand-based ceramic catalytic membranes prepared under optimal parameter conditions at different magnifications are shown in Figure 2. Figure 7e~Figure 7f The cross-sectional SEM images of manganese sand-based ceramic catalytic membranes prepared under optimal parameter conditions at different magnifications are shown in Figure 2. Figure 8a This is the particle size distribution diagram of manganese sand in the manganese sand-based ceramic catalytic membrane prepared under the optimal parameter conditions. Figure 8b The particle size distribution diagram of Al2O3 in the manganese sand-based ceramic catalytic membrane prepared under the optimal parameter conditions. The manganese sand and Al2O3 in the manganese sand-based ceramic catalytic membrane are evenly distributed, the manganese sand particles and Al2O3 particles are effectively fused, and the membrane surface and cross-sectional structure are uniform and complete. The removal effect of the manganese sand-based ceramic catalytic membrane on tetracycline at different concentrations in water is as follows Fig. 9As shown in the figure, it can be seen that the membrane can adapt well to the change of tetracycline concentration in water, and has a good catalytic effect in the range of tetracycline concentration of 0.8mg / L~10mg / L. Fig.10 As shown, it can be seen that with the increase in the amount of persulfate added as a strong oxidant, the reversible resistance and irreversible resistance of the manganese sand-based ceramic catalytic membrane are significantly reduced under its own catalysis, showing good anti-pollution ability.

[0072] The present embodiment provides a method for preparing a manganese sand-based ceramic catalytic membrane for water treatment, using manganese sand as the effective component of the ceramic catalytic membrane, and preparing the manganese sand-based ceramic catalytic membrane by mixing manganese sand and a matrix material, pressing the mixture, and sintering the mixture through a step temperature increase procedure. The catalytic ability of the manganese sand-based ceramic catalytic membrane prepared by the preparation method provided in the present embodiment comes from the rich Fe and Mn elements in the manganese sand. In addition to having the filtering and interception properties of general ceramic membranes, it can also catalyze oxidants such as ozone and persulfate to produce strong oxidizing species such as hydroxyl radicals, sulfate radicals, and singlet oxygen, oxidizing organic matter in water into small molecules, CO2, and H2O, and can efficiently adsorb Fe 2+ , Mn 2+ In addition, the manganese sand and the matrix material are pressed and sintered into one, the structural strength is large, there is no risk of cracking or falling off, the preparation method is simple, the manganese sand material is easy to obtain, and the preparation cost is low.

[0073] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A method for preparing a manganese sand-based ceramic catalytic membrane for water treatment, characterized in that: The following steps are involved: S1: grinding natural manganese ore to a preset particle size to obtain manganese sand; S2: mixing the manganese sand and the matrix material to obtain a mixed material; wherein the mass percentage of the manganese sand is 40% to 60%; and the matrix material comprises: Al2O3 with a particle size of 100nm to 1000nm; S3: Pressing the mixed material under a preset pressure to obtain a preform; S4: Sintering the preform through a step temperature increase program to obtain a manganese sand-based ceramic catalytic membrane.

2. The method for preparing a manganese sand-based ceramic catalytic membrane for water treatment according to claim 1, characterized in that: The method further includes the following steps between step S2 and step S3: Adding an auxiliary agent to the mixed material; the mass percentage of the auxiliary agent is less than or equal to 10%; the auxiliary agent includes: one or more of an adhesive, a lubricant and a performance optimizer; The performance optimizer is used to enhance the catalytic performance of the manganese sand-based ceramic catalytic membrane.

3. The method for preparing a manganese sand-based ceramic catalytic membrane for water treatment according to claim 2, characterized in that: The adhesive comprises: sodium carboxymethyl cellulose; The lubricant includes: glycerol; The performance optimizer includes: CuO.

4. The method for preparing a manganese sand-based ceramic catalytic membrane for water treatment according to claim 1, characterized in that: The preset pressure is 0.5MPa~150MPa.

5. The method for preparing a manganese sand-based ceramic catalytic membrane for water treatment according to claim 1, characterized in that: Step S4 includes: S401: calcining the preform at a temperature of 200° C. to 300° C. to obtain a calcined embryo body; S402: raising the temperature to 500° C. to 700° C. to calcine the calcined embryo body to obtain a calcined embryo body; S403: raising the temperature to 1000° C.-1200° C., sintering the calcined embryo body to obtain the manganese sand-based ceramic catalytic membrane.

6. The method for preparing a manganese sand-based ceramic catalytic membrane for water treatment according to claim 5, characterized in that: The time of the roasting and calcining is 0.5h~2h; The sintering time is 1h~4h.

7. The method for preparing a manganese sand-based ceramic catalytic membrane for water treatment according to claim 1, characterized in that: The preset particle size is less than or equal to 15 μm.

8. A manganese sand-based ceramic catalytic membrane for water treatment, characterized in that: The method is prepared according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of low-cost low-density catalytic functional ceramic membrane

    CN112316743A